Numerical investigation on the effect of the vessel rolling angle and period on the energy harvest. (February 2022) - Li, Boyang; Zhang, Rui; Yang, Qingyong; Zhang, Baoshou; Wang, Longjin
In order to harvest effectively the mechanical energy produced in the process of vessel rolling, an energy harvest unit installed on the vessel is designed to utilize the mechanical energy. Firstly, the structure of the unit is proposed, and the relevant mathematical model is established. The solution of the mathematical model is given by Newmark- β method. Then, the influence of vessel rolling period and angle on the unit's power and related parameters of the block is studied by MATLAB simulation. The results show that when the vessel is rolling, the energy harvest unit has a considerable power generation effect, the rolling period and angle of the vessel have a great impact on the power of the unit. Under the condition of the same period, the vessel with a larger rolling angle corresponds to larger peak gravity component, peak angular displacement, peak linear velocity of block and average power of the unit. In addition, under the same sea conditions, numerical simulations carried out on the rolling motion of 70, 000, 100, 000, and 150, 000-ton bulk vessels and related parameters of the unit, indicating that the instantaneous power of the unit is not uniform in actual sea conditions, but it can output power continuously.